A cross-sectional study to investigate the knowledge, attitudes, and current practices of pharmacovigilance, among medical doctors and pharmacists in South Africa - Rikhotso, Nyeleti Portia (Stellenbosch : Stellenbosch University, 2021)
Thesis (MMed)--Stellenbosch University, 2021.